Late pleistocene exploitation of Ephedra in a funerary context in Morocco - Morales, J; Carrión Marco, Y; Cooper, JH; Turner, E; Freyne, A; Hogue, J; Ziani, I; Barton, RNE; Bouzouggar, A; Humphrey, LT (Nature Research, 2024)
The active compounds found in many plants have been widely used in traditional medicine and ritual activities. However, archaeological evidence for the use of such plants, especially in the Palaeolithic period, is limited due to the poor preservation and fragility of seed, fruit, and other botanical macro-remains. In this study, we investigate the presence and possible uses of Ephedra during the Late Pleistocene based on the analysis of exceptionally preserved plant macrofossils recovered from c. 15 ka year-old archaeological deposits at Grotte des Pigeons in northeastern Morocco. This cave has yielded the earliest carbonized plant macrofossils of Ephedra, which were found concentrated in a human burial deposit along with other special finds. Ephedra is a plant known to produce high amounts of alkaloids, primarily ephedrine and pseudoephedrine, which have been utilized in traditional medicine. Direct radiocarbon dates on both Ephedra and the human remains indicate that they were contemporaneous. To understand the uses of Ephedra by people at the site, we discuss the different pathways through which plant remains could have arrived. We suggest that the charred cone bracts of Ephedra likely represent residues of the processing and consumption of the plant’s fleshy cones, which may have been valued for both their nutritional and therapeutic properties. Furthermore, we interpret the presence of Ephedra and its deposition in the burial area as evidence that this plant played a significant role during the funerary activities.